2014
DOI: 10.1007/s11069-014-1387-x
|View full text |Cite
|
Sign up to set email alerts
|

Field observation and numerical simulation of past and future storm surges in the Bay of Bengal: case study of cyclone Nargis

Abstract: Storm surges are one of the most important risks to coastal communities around the Bay of Bengal, and it is feared that the threat they pose will increase with climate change in the future. To understand the threats that these events pose, a summary of the field surveys performed in Yangon River Basin after cyclone Nargis in Myanmar in 2008 is presented. Though due to government restrictions survey activities were limited to the area near Yangon city, it was found out that the tide due to the storm surge was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Similar to this study, the simulated surge rises with enhancing the domain size primarily and then increases in constant value (Li et al 2013). Tasnim et al (2015) found that the simulated total water level was within the range of 3.5-4.6 m in most locations near the coast, whereas the observed maximum water level was within the range of 3.3-6.3 m. Surge wave occurred under the cyclone track due to the configuration of the coastline. Strong wind stresses were found at the end of the cyclone track.…”
Section: Simulation Of 2008 May Nargis Cyclonesupporting
confidence: 80%
See 2 more Smart Citations
“…Similar to this study, the simulated surge rises with enhancing the domain size primarily and then increases in constant value (Li et al 2013). Tasnim et al (2015) found that the simulated total water level was within the range of 3.5-4.6 m in most locations near the coast, whereas the observed maximum water level was within the range of 3.3-6.3 m. Surge wave occurred under the cyclone track due to the configuration of the coastline. Strong wind stresses were found at the end of the cyclone track.…”
Section: Simulation Of 2008 May Nargis Cyclonesupporting
confidence: 80%
“…Lwin (1980) pointed out that the notable storm surges experienced in Myanmar in the month of May with the cases of May 1967, May 1968, May 1970and May 1975. Most recent cyclone Nargis in 2008 made landfall in Myanmar, the most devastating storm, causing catastrophic destruction of about 10 million US dollar resulting in 140,000 casualties of its path (Tasnim et al 2015). In addition, the coastal regions of Myanmar are vulnerable to the loss of life and material, as these can be easily flooded by storm surges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adger 2006;Emrich and Cutter 2011;Dewan 2013;Islam et al 2016Islam et al , 2017. A number of studies have emphasized on the technical aspect and numerical modeling of tropical cyclone impacts (for example; Islam and Peterson 2008;Karim and Mimura 2008;Roy and Kovordányi 2012;Tasnim et al 2015;Hoque et al 2016Hoque et al , 2017bHoque et al , 2018. Hoque et al (2017a) systematically reviewed the researches on tropical cyclone disaster management using remote sensing and spatial analysis techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This contrasts to neighbouring countries, which have recently experienced several large disasters exceeding 5,000 casualties, contributing to raising awareness. This includes for example the 2004 Indian Ocean Tsunami [3], the 2008 Cyclone Nargis in Myanmar [4], the 2009 and 2010 tsunamis in Samoa and Mentawai [5][6][7], the 2011 Tohoku Earthquake Tsunami [8,9], and the 2013 Typhoon Haiyan in the Philippines [10,11].…”
Section: Introductionmentioning
confidence: 99%